A Bibliometric Analysis of 8,276 Publications During the Past 25 Years on Cholangiocarcinoma by Machine Learning - Zhang, Zeyu; Wang, Zhiming; Huang, Yun (Frontiers in Oncology, 2021)
Introduction: Cholangiocarcinoma (CCA) is the second common hepatic malignancy. Progresses and developments have also been made in the field of CCA management along with increasing scientific publications during the past decades, which reflects topics of general interest and suggests the future direction of studies. The purpose of this bibliometric study is to summarize scientific publications during the past 25 years in the field of CCA using a machine learning method. Material and methods: Scientific publications focusing on CCA from 1995 to 2019 were searched in PubMed using the MeSH term “cholangiocarcinoma”. Full associated data were downloaded in the format of PubMed, and extracted in R platform. Latent Dirichlet allocation (LDA) was adopted to identify the research topics from the abstract of each publication using Python. Results: A total of 8276 publications related to CCA from the last 25 years were found and included in this study. The most type of publications remained little changed, while the proportion of clinical trial remained relatively low (7.24% as the highest), and more significantly, with a further downward trend during recent years (1.42% in 2019). Neoplasm staging, hepatectomy and survival rate were the most concerned terms among diagnosis-related, treatment-related and prognosis-related. The LDA analyses showed chemotherapy, hepatectomy, and stent as the highly concerned research topics of CCA treatment. Meanwhile, conversions from basic studies to clinical therapies were suggested by a poor connection between clusters of treatment management and basic research. Conclusion: The number of publications of CCA increases rapidly during the past 25 years. Survival analysis, differential diagnosis, and microRNA expression are the most concerned topics in CCA researches. Besides, there are urgent needs of high-quality clinical trials and conversions from basic studies to clinical therapies.